Evaluating the impact of curfews and other measures on SARS-CoV-2 transmission in French Guiana - Alessio Andronico; Cécile Tran Kiem; Juliette Paireau; Tiphanie Succo; Paolo Bosetti; Noémie Lefrancq; Mathieu Nacher; Félix Djossou; Alice Sanna; Claude Flamand; Henrik Salje; Cyril Rousseau; et al. (Nature Communications, 2021)
Identifying effective combinations of control measures in different populations is important for SARS-CoV-2 control. Here, the authors show that in French Guiana, which has a relatively young population, curfews and localised lockdowns appeared to contribute to reducing transmission.